(untitled) (Sociología y tecnociencia, 2024)
The objective was to determine the relationship between soft skills and the adequacy of Peruvian companies in the face of the post-pandemic. The research was descriptive correlational with a non-experimental cross-sectional design, and an ad hoc checklist was used to record the information collected from the public retrievable material from business managers. It was identified that there is a statistically significant correlation between leadership and innovation with the adequacy of the companies; in addition, leadership, innovation, decision making and empathy of the managers better predict the adequacy of the companies in the post-pandemic period, as well as the soft skills as a whole.